Comparative analysis of the water diffusion in the corn grains, with and without pericarp during the thermo-alkaline treatment - Pineda-Gomez, Posidia; Rosales-Rivera, Andres; Gutierrez-Cortez, Elsa; Rodriguez-Garcia, Mario Enrique (Food and bioproducts processing, 2020)
[Display omitted] •The pericarp determined the diffusion dynamics of the solvents in the corn grain.•The diffusion coefficient showed an opposite behavior in corn grains with and without pericarp.•Simultaneous solvent diffusion and gelatinization occur when corn grain was submitted to thermo-alkaline treatment.•The water diffusion process in thermo-alkaline treatment looks slower in the whole corn grain due to the pericarp. In this research, the water diffusion in whole corn grain (with pericarp) and threshed corn grain (without pericarp) during thermo-alkaline treatment at different calcium hydroxide concentrations was studied, via measuring the moisture content as a function of time. The process was considered to be simultaneous unsteady-state water diffusion and first-order irreversible water-starch reaction (gelatinization) phenomenon. According to microscopy analysis, the alkaline solution solubilized the pericarp in the first stage of the process, generating micro-holes to allow the subsequent entry of water to the endosperm. For this reason, the whole grain showed a significant difference in the effective diffusivity in comparison to the threshed grain according to the diffusion coefficient (Deff) and the reaction rate constant (k) found in each of the concentrations used. The magnitude of the effective diffusion coefficient for threshed grain decreased from 1.46×10−10 to 1.29×10−10m2/s, as the concentration of calcium hydroxide was increased; this effective diffusion coefficient represents the water diffusivity in the corn endosperm. When the same model was applied in whole corn grain, an opposite trend was observed in this coefficient whose magnitude and increased from 7.24×10−11 to 7.92×10−11m2/s in the same concentration values; in this case, the coefficient represents not only the diffusivity in the endosperm but also the solubilization effect of the pericarp due to the alkaline solution. It has been concluded that the water diffusion mechanism was governed by the presence or absence of the pericarp during the cooking process. The analysis in-situ by DSC of starch gelatinization with alkaline solution showed that higher concentration delays the gelatinization beginning, and this concurs with a decrease in the effective diffusion coefficient in the endosperm of the grain without pericarp. The alkaline process increased the moisture, representing savings in cooking time.